A dataset consisting of a two-year long temperature and sound speed time series from acoustic tomography in Fram Strait - F. Geyer (Data in Brief, 2022)
Acoustic tomography systems provide an integrated, synoptic measurement of ocean temperature. By recording the time it takes for a sound signal to travel from a sound source to a receiver, the depth- and range-average sound speed along the geodesic path between the sound source and the receiver can be obtained through inversion. Sound speed and ocean temperature are empirically related; salinity plays a negligible role.The ACOBAR acoustic tomography experiment in central Fram Strait was carried out from September 2010 to September 2012. It consisted of 3 moorings with sound sources and receivers forming a triangle, and one mooring with only receivers in the middle. The steel-sphere flotation of the northernmost mooring imploded in the start of the experiment, so that mooring was not recovered. The three remaining moorings formed a smaller triangle that provided travel time measurements along three paths. Measurements were taken 8 times a day for two of the paths, 8 times every other day for the other paths. The distances covered by the acoustic measurements are 188 – 201 km.Complex data processing was used to determine peaks in the acoustic arrival coda and to correct them for mooring motion and clock drift; travel-time accuracy is O(10) ms. The travel time measurements were inverted to obtain range-depth average sound speed using a statistical approach. The sound speed obtained from each section was then converted to mean ocean temperature.The mean ocean temperature data are published as a set of 8 NetCDF files, compliant with Climate and Forecast (CF) [1] and OceanSITES metadata conventions [2]. Each file contains one year of measurements from one of the sections. The files contain the ocean temperature data, together with theoretical and statistical error estimates and metadata such as discovery metadata and adequate-use metadata. Each data point is provided with a statistical quality measure and a quality flag based on this measure.